The Effects of GABA, L-Theanine, Passiflora Incarnata and Prunus Cerasus in Reducing the Symptoms of Nervousness in Individuals with Anxiety and/or Depression - Lane, Gerry (Journal of Nutritional Therapeutics, 2014)
Introduction: Affecting more than 21 million American children and adults, anxiety with or without depression is the leading cause of disability in the USA for individuals ages 15 – 44. Treatment, traditionally has been with prescription medication that is addictive, prone to pharmaceutical abuse and if prescribed appropriately, requires intensive physician involvement and monitoring. The utilization of herbal supplementation has been successfully utilized for many years to treat mood disorders, however scientific analysis of benefits has been lacking. The objective of this study is to scientifically analyze the effectiveness of the combination of GABA, L-theanine, passiflora incarnata and prunus cerasus in the treatment of the symptoms associated with Anxiety. Methods: Two cohorts of volunteers received study compound (n=30) or placebo (n=30). Subjects were instructed to take 4 capsules daily for 7 consecutive days. Every participant completed both the HAM-A (Hamilton anxiety scale) and the SAS (Zung Self Rating Anxiety Scale). Both scales were completed pre & post study. The Student – T test was performed on all data. Results: HAM-A: Subjects receiving active study compound showed marked improvements in the HAM-A global score. SAS: The Zung SAS symptom scores of all subjects receiving active study compound were markedly improved. There were no side effects reported by any of the study participants. Conclusions: Subjects receiving this unique study compound (GABA, L-theanine, passiflora incarnata and prunus cerasus) received marked improvement in their symptoms of anxiety as demonstrated via two separate and clinically significant assessment tools (HAM-A & Zung SAS) when compared to placebo group. This combination of supplements represents a viable and safe adjunct to the short term treatment of mild to moderate anxiety without the use of prescription medication.